Investigating the quality management initiatives in higher educational institutions on customer satisfaction - Ayodele, Lasisi Abass; Mohd Ali, Hairuddin; Usman, Shuaibu Hassan (Central Research Insight, 2013)
With a mandate to general demand on quality education globally, educational administrators have increasingly embraced quality management as an important process through Deming theory of quality assurance for creating global staffs’ mind-sets on quality and to enhancing a profound quality achievement in Higher Education Institution (HEI). Meanwhile, HEI applaud this quality movement from the business to the field of education. With rises of fundamental question that is seldom asked when quality service in learning industries are chosen: “Is quality of particular HEI met customers’ expectations?” To respond to this question, the study presents perception of students in one of Malaysian university which engaging in organizational quality management initiatives. In this study, quantitative data collected investigating the extent the -PDCA of HEI in term of quality management initiatives met the customer expectation through Factor Analysis technique. It was observed that there is an increase in the quality culture of management, particularly in planning process and controlling strategies that enhances the increase resources for learning across multi-cultural students. Thus, study argues for further discussion and research about, consideration of large geographical institutions to stimulate generalization of quality management initiatives in learning institutions nationwide.